The incidence risk of programmed cell death-1/programmed cell death ligand 1 inhibitor-related alopecia for cancer patients: A systematic review and meta-analysis. Issue 42 (16th October 2020) - Li, Mingkai; Huang, Linlin; Ren, Xiuhong; Liu, Lixia; Shi, Qinghong; Liu, Ling; Wang, Xiao; Tian, Yuan; Yu, Lili; Mi, Fuli
Abstract: Purpose: To evaluate the incidence risk of programmed cell death-1/programmed cell death ligand 1 (PD-1/PD-L1) inhibitor-related alopecia for cancer patients, the meta-analysis was put into practice. Method: The meta-analysis was designed and put into practice according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Results: After rigorous screening and verification, 22 clinical trials involving PD-1/PD-L1 inhibitors were collected for the final comprehensive analysis. The incidence risk of alopecia for all-grade in the PD-1/PD-L1 group was significantly lower than that in the control chemotherapy group (odds ratio [OR] = 0.01, 95% confidence interval [CI]: [0.01, 0.04], I 2 = 86%, Z = 8.73 [ P < .00001]). Similar to the above, the incidence risk of alopecia for grade 3–5 related to PD-1/PD-L1 was obvious lower than the control group (OR = 0.17, 95% CI:[0.05, 0.55], I 2 = 0%, Z = 2.97 [ P = .003]). When 7 clinical trials (PD-1/PD-L1 + Chemotherapy vs Chemotherapy) were taken to evaluate the risk of alopecia for all-grade and grade 3–5, no statistically significant results were found. Conclusion: The incidence risk of alopecia caused by PD-1/PD-L1 is significantly lower than chemotherapy, and there is no statistical significant evidence that PD-1/PD-L1 combined with chemotherapy would increase the incidence risk of alopecia. Abstract : Supplemental Digital Content is available in the text